IDENTIFIKASI Mycobacterium tuberculosis PADA PENDERITA HIV/AIDS DI KOTA KENDARI - Wenty, Darmayanita; Sri Supadmi, Fracisca Romania; Waly, Sry Waly (Program Study of Medical Laboratory Technology , Politeknik Bina Husada Kendari, 2023)
ABSTRACT Human Immunodeficiency Virus (HIV) is a RNA retrovirus that attacks the human immune system. This virus infects cells that have Cluster of Differentiation 4 (CD4) molecules, especially T lymphocytes that have receptors with high affinity for HIV. HIV virus can cause some opportunistic infections one of them tuberculosis. Tuberculosis is a chronic infection caused mainly by Mycobacterium tuberculosis. This study aims to determine the results of identification of Mycobacterium tuberculosis of people with HIV / AIDS in Kendari City. This study was carried out in the Microbiology Laboratory of Bina Husada Polytechnic Kendari. Type of this study is semi-quantitative with the sampling technique by accidental sampling as many as 10 samples. The examination used Acid Resistant Basil (BTA) and the method used Ziehl Neelsen with the results obtained did not found smear in 100 visual fields (negative) for all samples. Based on the research that has been carried out, it could be concluded that the examination of Mycobacterium tuberculosis in HIV / AIDS sufferers in Kendari City obtained negative results (-) for all samples. Key words: HIV, AIDS, TB, Mycobacterium tuberculosis ABSTRAK Human Immunodeficiency Virus (HIV) merupakan retrovirus golongan RNA yang menyerang kekebalan tubuh manusia. Virus ini menginfeksi sel yang mempunyai molekul Cluster of Differentiation 4 (CD4) terutama limfosit T yang memiliki reseptor dengan afinitas yang tinggi untuk HIV. Virus HIV dapat mengakibatkan beberapa infeksi oportunistik salah satunya tuberkulosis. Tuberkulosis adalah penyakit infeksi kronis terutama disebabkan oleh Mycobacterium tuberculosis. Penelitian ini bertujuan untuk untuk mengetahui hasil identifikasi Mycobacterium tuberculosis pada penderita HIV/AIDS di Kota Kendari. Penelitian ini dilaksanakan di Laboratorium Mikrobiologi Politeknik Bina Husada Kendari. Jenis penelitian ini adalah semi kuantitatif dengan teknik pengambilan sampel secara accidental sampling sebanyak 10 sampel. Pemeriksaan menggunakan pewarnaan Basil Tahan Asam (BTA) dengan metode Ziehl Neelsen dengan hasil yang diperoleh tidak ditemukan BTA dalam 100 lapang pandang (negatif) untuk semua sampel. Berdasarkan penelitian yang telah dilakukan diperoleh kesimpulan bahwa pemeriksaan Mycobacterium tuberculosis pada penderita HIV/AIDS di Kota Kendari diperoleh hasil negatif (-) untuk semua sampel. Kata Kunci : HIV, AIDS, TB, Mycobacterium tuberculosis